USING THINK-PAIR-SQUARE-SHARE STRATEGY TO IMPROVE STUDENTS’ SPEAKING ABILITY FOR INDONESIAN SENIOR HIGH SCHOOL STUDENTS - Devi Rufiana; Mulyadi Mulyadi (Universitas Bengkulu, 2017)
The objective of the research was to determine how the Think-Pair-Square-Share (TPSS) Strategy can improve the frequency, duration and accuracy speaking students. The subject wasthe second year of Language class, consists of 19 students. The quantitative and qualitative data were applied to see the improvement of students’ speaking ability and improvement of learning situations for the strategy applied. The instruments used to gather the data werea students’ speaking ability test and observation sheet. Based on the results of the test conducted at the end of the study and analysis of observation sheets, it could be said that the speech and behavior of students during the learning process had increased. The students' speaking frequency, duration and accuracy orderly increasedfrom 31%, 47%, and 37% at baseline to 79%, 84% and 79% at the end of the study. Results showed that the number of students at the end of the research had achieved success indicator. The students also showed motivation, interest, participation, and enthusiasm better for the learning process.